Rethinking Management of the 21st Century: Аn Approach to Contemporary Business Education - Kuzin, Dmitry V. (Revista Eduweb, 2021)
This paper is addressing the issues of modern management thinking which became one of the most critical tasks in contemporary business education. Such thinking must reflect all major changes and challenges in science, technology, economy, politics, culture, and society which took place within the first two decades of the 21st century and especially now in the times of pandemic crisis. It is very important not only in terms of analysis but also as an explanation of the patterns of business and management behavior. It became the topic of serious scientific debate of the most prominent business researchers and consultants. The purpose of the article is to develop the methodological approach for further research of modern management and suggest the conceptual model which could structure the analysis of contemporary business reality. The author suggests the conceptual model for further research which could explain the essence of new management revolution. Such open model could be added and interpreted and is already applied in different educational programs in Russia.